A novel acceleration method for molecular dynamics of crystal silicon on GPUs using OpenACC. (19th July 2022) - Liang, Jianguo; Fu, You; Hua, Rong; Zhang, Hao; Zhu, Wenqiang; Ye, Yuxi
Abstract: Compared with CUDA and OpenCL, OpenACC has the advantages of simple programming, openness, and good portability for GPU acceleration. An OpenMP/OpenACC implementation for molecular dynamics of silicon crystal on GPUs is proposed. First, to make effective use of vectorization and streaming, data structure conversion and data dependence elimination are designed. Second, the parallel version on the single GPU is realized by adding OpenACC guidance sentences, with very few modifications. Third, a patch block strategy is proposed to realize the parallel version on single machine multi‐GPUs using OpenMP+OpenACC, which greatly simplifies the construction of shadow area and the exchange of shadow area data. Experimental results show that 23 to 25 speedup is achieved for the single GPU at different scales over the serial program on Intel(R) Xeon(R) CPU E5‐2690 v4, and 6.37 speedup is achieved over the single GPU when the number of atoms reaches 2, 097, 152 on 8GPUs on single machine.